Anthropometric variables and vertical jump in male frisbee players due to game's position / Zulkifli Ismail … [et al.] - Ismail, Zulkifli; Ismail, Anis Syaimaa Husna; Mohd Salleh, Asrul; Jamaludin, Masshera; Abu Talip, Nur Khairunisa; Md Razali, Mohd Rizal (Universiti Teknologi MARA, Pahang, 2022)
The vertical jump is one of the necessary variables in performing offence and defence skills in ultimate frisbee. The purpose of this study was (1) to compare vertical jumps among frisbee players based on the game's position (2) to determine the relationship between anthropometric variables and vertical jumps. A total of 16 male ultimate Frisbee players from a top team in Malaysia were recruited as participants, and at least they played for two years for that team (23.19 ± 2.07 years old, 3.44 ± 2.45 years' experience). The data was collected in two sessions. Eleven anthropometric variables: stature, body mass, tronchanterion-tibiale lateral, tibiale lateral height, leg length, foot length, mid-thigh girth, calf girth max acromiale-radiale, radiale-stylion radiale, and midstylion-dactylion were measured using SECA tailor tape. The jumping height was measured with a VERTEC jumping apparatus and converted into peak power output using Sayers Equation. One-way ANOVA was utilized to determine differences in the mean vertical jump of the handler, mid, and deeper, and the Pearson correlation coefficient was used. Peak power output significantly correlated with body mass, leg length, radiale-stylion radiale, and midstylion-dactylion on three game positions. Results show vertical jump mean score (48.00 ± 1.00cm) of the deepers position was significantly different from handlers' position (44.17 ± 3.19cm), considering to game's position seems to be necessary for ultimate Frisbee players to catch and tap the disc successfully.